Metabolic and mechanical characteristics of Olympic female gold medalist - Ogita, F.; Tanaka, T.; Tamaki, H.; Wagatsuma, A.; Hamaoka, T.; Toussaint, H. M. (Biomechanics and Medicine in Swimming X, 2006)
To clarify metabolic and mechanical characteristics of a superior swimmer, an Olympic gold medalist was compared to 16 elite Japanese college swimmers who belonged to an inter-college champion team. Maximal oxygen uptake (V02max), maximal blood lactate concentration (LAmaxl), a drag coefficient, a drag exponent, drag-swimming speed relationship and maximal propulsive power (MPP) were determined. In the comparison ofv02max, LAma" and MPP, no marked differences were observed between the gold medalist and the other swimmers. On the other hand, the drag-swimming speed relationship revealed lower drag for the gold medalist, especially at higher swimming speed (near race pace). Taken all, it is suggested that mechanical (technical) factors, such as propelling efficiency and the stroke technique to reduce drag, should be considered as more significant determinants of superior swimming performance.